2011
DOI: 10.1155/2011/217378
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Carcinomas in Gorlin Syndrome: A Review of 202 Patients

Abstract: Gorlin syndrome (Naevoid Basal Cell Carcinoma Syndrome) is a rare autosomal dominant syndrome caused by mutations in the PTCH gene with a birth incidence of approximately 1 in 19,000. Patients develop multiple basal cell carcinomas of the skin frequently in early life and also have a predisposition to additional malignancies such as medulloblastoma. Gorlin Syndrome patients also have developmental defects such as bifid ribs and other complications such as jaw keratocysts. We studied the incidence and frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
139
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(152 citation statements)
references
References 18 publications
6
139
1
6
Order By: Relevance
“…The causative mutations have been found to be in the sonic hedgehog pathway, including PTCH1 [22,23], PTCH2 [24], and SUFU [25], with PTCH1 mutation being found in 60-75 % of NBCCS patients [6,26]. Although it is a genetic disease, about 35-50 % of affected patients represent new mutations [5].…”
Section: Discussionmentioning
confidence: 99%
“…The causative mutations have been found to be in the sonic hedgehog pathway, including PTCH1 [22,23], PTCH2 [24], and SUFU [25], with PTCH1 mutation being found in 60-75 % of NBCCS patients [6,26]. Although it is a genetic disease, about 35-50 % of affected patients represent new mutations [5].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Distinguishing facial features associated with the syndrome include milia, macrocephaly, bossing of the forehead, coarse facial features and hypertelorism. [2][3][4] Palmar and plantar pits and calcification of the falx cerebri are common characteristic findings. [2][3][4] Other significant complications include childhood medulloblastoma, ovarian and cardiac fibromas, 2 ocular anomalies, and cleft lip and palate.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Palmar and plantar pits and calcification of the falx cerebri are common characteristic findings. [2][3][4] Other significant complications include childhood medulloblastoma, ovarian and cardiac fibromas, 2 ocular anomalies, and cleft lip and palate. 4 One of the main defining features of Gorlin syndrome is the early onset of multiple BCCs, 4 with a median age of onset of 25 years.…”
Section: Introductionmentioning
confidence: 99%
“…Exonic, multiexonic, and whole-gene deletions have been reported in about 6% of individuals with NBCCS [Evans and Farndon, 2002]. The studies of disease prevalence come from the UK population, where it is nearer to 1:30,827 [Evans et al, 2010]; The actual figure could be higher still, since less severe cases may not be diagnosed and Jones et al [2011] recently reported an incidence of 1 in 19,000 births.…”
Section: Introductionmentioning
confidence: 99%